The Effect Of Employee Engagement, Career Development, And Compensation On Employee Job Satisfaction At The National Narcotics Agency Of Binjai City - Dedek Mulya Ardana; Muhammad Yalzamul Insan; Wilchan Robain (Journal of Management, Economic, and Accounting, 2026)
This research seeks to examine the effects of employee engagement, career development, and compensation on job satisfaction among employees at the National Narcotics Agency (BNN) of Binjai City. A quantitative approach with an associative design was employed. The population consisted of all 42 employees of BNN Binjai City, and a saturated sampling technique was applied, meaning the entire population served as the research sample. Data were collected using a Likert-scale questionnaire. The data were analyzed through validity and reliability testing, classical assumption testing, multiple linear regression, partial tests (t-test), simultaneous testing (F-test), and the coefficient of determination (R²). The findings from the multiple linear regression reveal that, individually, employee engagement, career development, and compensation each exert a positive and statistically significant influence on job satisfaction, as indicated by significance levels below 0.05. The simultaneous test further demonstrates that these three variables collectively have a positive and significant impact on job satisfaction, with a significance value lower than 0.05. In addition, the coefficient of determination (R²) shows that employee engagement, career development, and compensation account for a substantial proportion of the variance in employee job satisfaction, while the remaining variance is explained by other factors not included in this study. These results suggest that strengthening employee engagement, implementing well-structured career development programs, and providing fair and proportional compensation systems are key factors in enhancing employee job satisfaction at the National Narcotics Agency of Binjai City.